Systematic Literature Review: Gamification as a Learning Approach in Christian Religious Education in the Digital Age - Prilly Lastika Manuputty; Deka Dyah Utami; I Nyoman Sudana Degeng (Teknodika, 2025)
The rapid development of technology has advanced education, including the use of gamification as an innovative learning approach. Gamification integrates game elements to enhance students' interest and motivation and can be applied in various subjects, including Christian Religious Education. However, teaching methods in Christian Religious Education often remain traditional and monotonous. This study aims to encourage teachers to implement gamification in their teaching process. The research uses the Study Literature Review (SLR) method, collecting data from 12 relevant articles obtained through Google Scholar and Publish or Perish (POP). The findings show that gamification creates an engaging, interactive, and dynamic learning environment, improving students' motivation, participation, and learning outcomes across cognitive, affective, and psychomotor domains. Technology-based gamification enhances students' understanding based on their learning styles and fosters collaboration. However, its effectiveness depends on careful planning and relevant content selection. Without proper design, gamification may become a challenge rather than a benefit. Platforms like Kahoot have been widely used in education, offering interactive real-time quizzes that boost engagement and cooperation among students. Ultimately, gamification not only increases motivation but also transforms the learning experience into a more interactive and enjoyable process.